ChemInform Abstract: One‐Pot Unsymmetrical Ketone Synthesis Employing a Pyrrole‐Bearing Formal Carbonyl Dication Linchpin Reagent. Issue 52 (10th December 2015) - Heller, Stephen T.; Newton, James N.; Fu, Tingting; Sarpong, Richmond
Abstract: A wide range of ketones and Weinreb amides are synthesized from various organolithium and Grignard reagents in one‐pot without the need of a transition‐metal catalyst.